The Dublin housing question: sanitary and insanitary - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1913)
So much attention has been devoted to the insanitary condition of certain quarters of our City that it appears to me that the work which has been done for the providing of sanitary and comfortable dwellings for the workers has been almost completely overlooked. In the first place, I desire to point out what has been done for the providing of Sanitary dwellings. In the second, I shall deal with what are called the Slums. Amongst the greatest of pioneers and reformers in the housing of Dublin stands the Corporation.
Read May 16th, 1913.
Keywords: Dublin tenements; Charitable housing; Slums, Dublin; Public housing; 314.15